Identification of the genetic determinants of shovel-shaped incisors and Carabelli’s cusp - Erbil, Fatma Nur; Merriwether, David Andrew (Anthropological Review, 2024)
Shovel-shaped incisors (SSI) and Carabelli’s cusp (CC) are noteworthy human dental non-metric traits which presence and degree of expression have been reported to cluster within distinct populations. Recent advances in developmental biology suggest that SSI and CC are likely under polygenic developmental control; therefore, genetic variation in multiple genes is likely to contribute to differential SSI and CC expression. The exact genetic mechanisms underlying variation in SSI and CC development, however, remain mostly unknown. This study aims to identify whether variation in the basal DNA sequences of six candidate genes, NKX2-3, SOSTDC1, BMP4, FGF3, FGF4, and WNT10A, has any impact on SSI and/or CC expression. Study methods involve collection of saliva samples and dental data from 36 participants. The Arizona State University Dental Anthropology System (ASUDAS) has been used to score SSI and CC expression. Next-generation sequencing (NGS) methods were utilized to sequence the entire gene region of the candidate genes. Spearman’s correlation test was used to score the relationship between the genotype and degree of trait expression of participants. Fifteen SNPs/INDELs belonging to SOSTDC1, FGF3, FGF4 and WNT10A were significantly associated with SSI and/or CC expression. No SNPs/INDELs were detected in the genes BMP4 and NKX2-3 that significantly contributes to observed phenotypes. FGF3, FGF4, SOSTDC1 and WNT10A were possibly involved in the formation of shoveling and Carabelli’s cusp. However, because of the small sample size, more studies are needed to confirm their role and rule out any potential role of NKX2-3 and BMP4 in the production of SSI and CC.